Waste floral foam to nanoporous activated carbon for efficient CO2 capture: An investigation on the property-performance correlation of KOH impregnation - Akshata Pattanshetti; Vidhya Jadhav; Amruta Koli; Miroslaw Kwiatkowski; Radha Kishan Motkuri; Deok-kee Kim; Sandip Sabale (Waste Management Bulletin)
The efficient CO2 capture requires engineering a low-cost, highly efficient adsorbent. Herein, the upcycling of waste floral foam into chemically activated nanoporous carbon (CANC) is reported. The implications of the impregnation ratio of KOH on the porosity, surface functionality of CANC, and its role in CO2 capture are examined and discussed. The optimized sample, CANC-2 (SSA 1043 m2/g), with a large ultra-micropore volume and higher oxygen and nitrogen content, demonstrates 3.71 mmol/g CO2 capture capacity at 15 ℃ and 1 atm. The framework provided here offers a technique for tuning the attributes of nanoporous carbon favorable for CO2 capture. Ultimately, the pollution control of solid polymeric waste can be done by upcycling it into value-added products which further utilized in environmental applications.